2015
DOI: 10.1177/0363546515611661
|View full text |Cite
|
Sign up to set email alerts
|

Medial Patellofemoral Ligament Injuries in Children With First-Time Lateral Patellar Dislocations

Abstract: Skeletally immature children are more prone to sustaining an MPFL injury at the patellar attachment site. Arthroscopic surgery and MRI complement each other in the investigation of MPFL injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 34 publications
2
59
0
3
Order By: Relevance
“…A recent MRI study demonstrated that nearly 100% of pediatric patients have structural damage to the MPFL following a single patellar dislocation [2]. MPFL injury combined with baseline structural abnormalities likely account for the high rate of recurrent patellar instability in the ipsilateral knee (compared to the contralateral knee).…”
Section: Discussionmentioning
confidence: 99%
“…A recent MRI study demonstrated that nearly 100% of pediatric patients have structural damage to the MPFL following a single patellar dislocation [2]. MPFL injury combined with baseline structural abnormalities likely account for the high rate of recurrent patellar instability in the ipsilateral knee (compared to the contralateral knee).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies have looked at the site of MPFL injury: patella, interstitial, femur, or a combination of those sites [3,7,17,22,23,42,43]. Knowing the location is important because the rate of redislocation is higher when there is an isolated femoral lesion [22,35] and acute repair may fare better when the lesion is solely patella based [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MRI is of prime importance to localize possible medial patellofemoral ligament (MPFL) tears, which can be patellar, femoral or multifocal. In young children (aged 9 to 14), the patellar attachment site is the most commonly damaged, occurring a total rupture in more than half of the cases [9]. The second topic prone to discussion refers to treatment.…”
Section: Discussionmentioning
confidence: 99%